2016
DOI: 10.1038/srep26885
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of polygenic effects links primary open-angle glaucoma and age-related macular degeneration

Abstract: Primary open-angle glaucoma (POAG) and age-related macular degeneration (AMD) are leading causes of irreversible blindness. Several loci have been mapped using genome-wide association studies. Until very recently, there was no recognized overlap in the genetic contribution to AMD and POAG. At genome-wide significance level, only ABCA1 harbors associations to both diseases. Here, we investigated the genetic architecture of POAG and AMD using genome-wide array data. We estimated the heritability for POAG (h2g = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
3
17
1
1
Order By: Relevance
“…Testing our dataset for this possibility showed that the association of the genetic scores in the population-based studies remained unchanged when comparing to the entire data including case-control studies with the exception of the VCDR and MYP genetic scores. From this, we conclude that AMD patients indeed have a genetically reduced risk to develop open angle glaucoma, although a smaller study found an adverse relationship between AMD and POAG using summary statistics [110]. Conversely, we found no association of the myopia genetic score with AMD in our dataset in the population-based studies, in line with previous reports [111114].…”
Section: Discussionsupporting
confidence: 91%
“…Testing our dataset for this possibility showed that the association of the genetic scores in the population-based studies remained unchanged when comparing to the entire data including case-control studies with the exception of the VCDR and MYP genetic scores. From this, we conclude that AMD patients indeed have a genetically reduced risk to develop open angle glaucoma, although a smaller study found an adverse relationship between AMD and POAG using summary statistics [110]. Conversely, we found no association of the myopia genetic score with AMD in our dataset in the population-based studies, in line with previous reports [111114].…”
Section: Discussionsupporting
confidence: 91%
“…Analyses of firstdegree relatives of POAG patients have shown that the sib relative risk is 10.4 6 2.5 (5). Classic twin studies in POAG are lacking and there is no consensus on heritability for POAG, but work by Cuellar-Partida et al estimated the heritability of POAG based on genome-wide array data at 0.42 6 0.09 (6). Several genome-wide association studies (GWAS) have identified new POAG genes by examining POAG directly or studying endophenotypes like VCDR and IOP (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…4 We found that the genetic correlation estimated from markers genome-wide was substantially less than 1 (correlation 0.33, with standard error 0.24). Our findings on POAG are in contrast to findings across other complex traits, where the genome-wide genetic correlation between males and females is typically close to 1.…”
mentioning
confidence: 99%
“…It is also likely that some of the difference in POAG prevalence between sexes is due to heritable factors. However, as for our finding at 9p21 we have only estimated the genome-wide genetic correlation in one population (Australians of European ancestry 4 ). It would be interesting to investigate sex differences genome-wide in other populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation